A Rash Decision: Implementing an EHR-Integrated Penicillin Allergy Delabeling Protocol without Adequate Clinician Support - Plattner, Alexander S.; Lockowitz, Christine R.; Same, Rebecca G.; Abdelnour, Monica; Chin, Samuel; Cormier, Matthew J.; Daugherty, Megan S.; Grier, Alexandra E.; Hampton, Nicholas B.; Hofford, Mackenzie R.; Mehta, Sarah S.; Newland, Jason G.; O'Bryan, Kevin S.; Sattler, Matthew M.; Shah, Mehr Z.; Starnes, G Lucas; Yuenger, Valerie; Ellis, Alysa G.; Facer, Evan E. (Applied Clinical Informatics, 2025)
Approximately 10% of patients have a documented penicillin “allergy”; however, up to 95% have subsequent negative testing. These patients may receive suboptimal antibiotics, leading to longer hospitalizations and higher costs, rates of resistant and nosocomial infections, and all-cause mortality. To mitigate these risks in children, we implemented an inpatient penicillin allergy delabeling protocol and integrated it into the electronic health record (EHR) through a mixed methods approach of clinical decision support (CDS).We describe our protocol implementation across three sequential phases: “Pilot,” “Active Antimicrobial Stewardship Program (ASP),” and “Mixed CDS.” We highlight several potential pitfalls that may have contributed to poor clinician adoption.Patients were risk-stratified as nonallergic, low-risk, or high-risk based on history. Process measures included: evaluation rate, oral challenge rate for low-risk, and allergy referral rate for high- or low-risk when oral challenge was deferred. The primary outcome measure was the penicillin allergy delabeling rate among low-risk or nonallergic. Balancing measures included the rate of epinephrine or antihistamine administrations.The pilot and ASP phases used clinician education and an order set, but were mostly manual processes. The mixed CDS phase introduced interruptive alerts, dynamic text in note templates, and patient list columns to guide clinicians, but little education was provided. The mixed CDS phase had the lowest evaluation rate compared with the pilot and active ASP phases (6.4 vs. 25 vs. 15%). However, when the evaluation was performed, the mixed CDS phase had the highest oral challenge rate (33 vs. 26 vs. 13%) and delabeling rate (43 vs. 33 vs. 27%). No adverse events occurred.CDS tools improve clinician decision-making and optimize patient care. However, relying on CDS for complex clinical evaluations can lead to failure when clinicians cannot find the tool or appreciate its importance. Person-to-person communication can be vital in establishing a process and educating intended users for successful CDS implementation.
Keywords: clinical decision support; penicillin allergy delabeling; pediatrics; antimicrobial stewardship